Cost-effectiveness analysis of COPD screening programs in primary care for high-risk patients in China - Shuli Qu (Nature Portfolio, 2021)
Abstract We built a decision-analytic model to compare the cost-effectiveness of using portable spirometer and questionnaire to screen chronic obstructive pulmonary diseases (COPD) with no screening (i.e. usual care) among chronic bronchitis patient in China. A lifetime horizon and a payer perspective were adopted. Cost data of health services including spirometry screening and treatment costs covered both maintenance and exacerbation. The result indicated that portable spirometer screening was cost-saving compared with questionnaire screening and no screening, with an incremental cost-effectiveness ratio (ICER) of −5026 and −1766 per QALY, respectively. Sensitivity analyses confirmed the robustness of the results. In summary, portable spirometer screening is likely the optimal option for COPD screening among chronic bronchitis patients China.